Founding Editorial — Atmospheric Systems and TheScientificWorld - Peter Brimblecombe; John G. Watson (The Scientific World Journal)
There is a satisfying logic to the Greek choice of air, water, and earth as elements. Today we see this logic reflected in the way that that global science is subdivided into the categories of air, land, and water. Thus, the relevance of a science of global issues is not merely of academic interest. The tide of environmental concern, a vision of limits to growth, and a desire for sustainability have fostered an unprecedented interest in global sciences.